Perencanaan Pemanfaatan Potensi Lokal dalam Membangun Desa Wisata dengan Pendekatan Konsep Community Based Tourism (CBT) di Desa Bumi Rahayu - Budiarti, Ika Niswatin; Imelda, Dewi Qomariah; Soimah, Nurus; Alfiansyah, Muhammad (Keris: Journal of Community Engagement, 2024)
This activity aims to mobilize community participation in planning and utilizing the local potential of Bumi Rahayu Village to develop a Tourism Village. Through the Community Based Tourism (CBT) concept approach, it is hoped that it can strengthen the involvement of local communities in destination management, improve the welfare of local communities, and preserve culture and the environment. The methodology in this service is to provide knowledge and understanding of the potential of villages and tourist villages using discussion methods, field surveys and creating tourism concepts. This activity produces an overview of the tourism concept of the Bumi Rahayu river flow by optimizing the natural wealth around it. The description given focuses on land use to increase tourist attraction, such as the placement of entrance gates, parking locations, "kios wisata" locations, photo spot locations, toilet locations, gazebo locations and campground locations. The photo booth and gazebo will be built using ecobrick products as a concrete step in utilizing plastic waste produced by TPS3R Bumi Rahayu in collaboration with PKH recipients and the wider community. Utilizing local potential to become a tourist destination with a Community Based Tourism (CBT) approach in Bumi Rahayu Village has the aim of developing a sustainable tourism village. Through collaboration with local communities, this plan aims to optimize local resources and heritage, create economic opportunities, and promote positive interactions between tourists and local communities. This planning supports the development of a competitive tourist village which will later become one of the famous tourist destinations in Bulungan Regency and increase the income of the people in Bumi Rahayu Village, Bulungan Regency.